Dynamic stiffness model of spherical parallel robots. (8th December 2016) - Cammarata, Alessandro; Caliò, Ivo; D׳Urso, Domenico; Greco, Annalisa; Lacagnina, Michele; Fichera, Gabriele
Abstract: A novel approach to study the elastodynamics of Spherical Parallel Robots is described through an exact dynamic model. Timoshenko arches are used to simulate flexible curved links while the base and mobile platforms are modelled as rigid bodies. Spatial joints are inherently included into the model without Lagrangian multipliers. At first, the equivalent dynamic stiffness matrix of each leg, made up of curved links joined by spatial joints, is derived; then these matrices are assembled to obtain the Global Dynamic Stiffness Matrix of the robot at a given pose. Actuator stiffness is also included into the model to verify its influence on vibrations and modes. The latter are found by applying the Wittrick–Williams algorithm. Finally, numerical simulations and direct comparison to commercial FE results are used to validate the proposed model.